Gag Reflex-Mediated Restoration of Sinus Rhythm during TEE Probe Insertion for Atrial Fibrillation: A Word of Caution - Zeid Nesheiwat; Marcel Ghanim; Joseph Eid; Neha Patel; Cameron Burmeister; Ehab Eltahawy (Case Reports in Cardiology)
It is recommended to attempt vagal maneuvers as initial therapy in various types of supraventricular tachycardia. While various forms of vagal techniques have been described, a gag reflex-mediated vagal technique, to the best of our knowledge, has not been. We present a case of gag reflex-mediated restoration of sinus rhythm in a patient with atrial fibrillation and rapid ventricular response upon transesophageal probe insertion. This case is unique due to the mechanism of vagally mediated cardioversion. It emphasizes that operators must be cautious regarding the risk of embolization of a potential thrombus from vagal-mediated cardioversion with unknown thrombus burden.